Determining the valine requirement of the mgr-producing lactating sow - Richert, B.T.; Pettigrew, J.E.; Walker, R.D.; Johnston, L.J.; Blum, S.A.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred-three large white x Landrace or large white x Chester White x Landrace sows (40 or 41/treatment, avg parity 3.7) were used in a 26 d lactation experiment to determine the valine requirement of high-producing sows. All diets were formulated to .9% lysine with all amino acids other than valine formulated to be at least 110% of their respective ratios relative to lysine. Synthetic valine replaced cornstarch to provide .75, .85, .95, 1.05, and 1.15% dietary valine. Corresponding valine:lysine ratios were 83, 94, 106, 117, and 128% of lysine. The experiment was conducted at two experiment stations from July, 1993 through January, 1994. Mean litter size of all treatments after adjustment was 10.33 pigs. Sow feed intake and grams of lysine intake were not different among treatments. Grams of valine intake increased linearly as dietary valine increased. Litter weight at d 21 and weaning increased linearly with increasing dietary valine. Litter weight gain from d 0 to 7 increased linearly as dietary valine increased to 1.15 %. Litter weight gain from d 0 to 21 and d 0 to weaning increased linearly as dietary valine increased, with the greatest portion of the response observed as valine increased to 1.05% of the diet. Dietary valine had no effect on sow weight change, 10th rib backfat (BF) change, or last lumbar BF change from d 0 to 21 or d 0 to weaning. Days to estrus postweaning were not affected by dietary valine. These results demonstrate that high-producing sows have a dietary valine requirement of at least 117% of lysine during lactation (66.4 g/d valine), much greater than is currently recommended by NRC (1988; 100% of lysine) or ARC (1981; 70% of lysine) to maximize litter weaning weight and litter weight gain.
Keywords: Swine; Valine; Lactation; Sows